Rising to the Challenge: Top Executives with R&D Background, Risk-Taking and Corporate Innovation. (June 2022) - Li, Huicong; Xiang, Erwei
More than half of Chinese high-technology firms are led by top executives (chairman and CEO) with R&D background. This study investigates whether and how top executives' R&D background affects corporate innovation outcomes using a sample of listed firms in the high-technology industries in China. We find that the R&D background of top executives is positively related to innovation outcomes. We also find evidence on the mediating effect of R&D expenditure and moderating effect of corporate risk-taking on the above relationship. Our baseline results are robust to tests that address concerns caused by potential unobservable characteristics, reverse causality and other issues. Findings of our study have important implications for firms that aim to enhance their innovation outcomes and countries regarding their research policymaking and R&D management.